Exterior view of Mulaprasada of the Suhaveshwar Temple - Temples of India Project Team (Jio Institute, 2024)
This is the south-facing elevation of the mulaprasada (main shrine) of the Suhaveshwar Temple. The juncture where the mandapa (pillared hall) meets the main shrine has a plain wall with only one band of ornamentation at the centre. This forms the kapili that corresponds to the antarala (vestibule or antechamber) of the temple. The jangha (wall) of the temple is plain, divided into two parts by a plain band.